Answered

Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Simplify the expression:

–5(6 − 2y) =


Sagot :

-30+10y
hope this helps!

Answer:

3

Step-by-step explanation:

-5(6-2y)

-30+10y=0

10y=30

y=3